2013
DOI: 10.3109/00016489.2013.831994
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic ultrasound features of mucosa-associated lymphoid tissue lymphoma of the salivary and thyroid gland

Abstract: Two ultrasound patterns were observed for MALT lymphoma. The first was characterized by a marked hypoechoic area with interspersed linear echogenic strands (linear echogenic strands pattern), and the second was characterized by multiple, relatively large, hypoechoic segments (segmental pattern). Histopathologically, these patterns could be explained on the basis of the expansion of lymphoma cells demarcated by narrow or wide fibrous bands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Determining the underlying pathologic characteristics of primary thyroid lymphoma could lead to a reasonably specific sonographic category for this disease. Recently, sonographic findings of primary thyroid lym-phoma were correlated with pathologic findings in studies by Orita et al 3 and Nam et al 4 Both studies showed that the hypoechoic areas of primary thyroid lymphoma were consistent with lymphoepithelial lesions containing neoplastic cells, whereas echogenic structures within or around the lesions were consistent with fibrotic tissue. Therefore, primary thyroid lymphoma lesions should histopathologically include lymphoma cells and reactive connective tissue.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Determining the underlying pathologic characteristics of primary thyroid lymphoma could lead to a reasonably specific sonographic category for this disease. Recently, sonographic findings of primary thyroid lym-phoma were correlated with pathologic findings in studies by Orita et al 3 and Nam et al 4 Both studies showed that the hypoechoic areas of primary thyroid lymphoma were consistent with lymphoepithelial lesions containing neoplastic cells, whereas echogenic structures within or around the lesions were consistent with fibrotic tissue. Therefore, primary thyroid lymphoma lesions should histopathologically include lymphoma cells and reactive connective tissue.…”
Section: Discussionmentioning
confidence: 85%
“…An early diagnosis of primary thyroid lymphoma can lead to timely treatment and a favorable prognosis 2 . However, there are few reports about the sonographic features of primary thyroid lymphoma, and the results have had some disparity 3 – 9 . In addition, its Doppler flow pattern was not known.…”
mentioning
confidence: 99%
“…However, sialolithiasis shows stones Satomi Omotehara 6 with acoustic shadows in the dilated ducts. Malignant lymphomas, especially mucosa-associated lymphoid tissue lymphoma (MALT lymphoma), show hypoechoic areas with rough or dense linear echogenic strands and a lobulated shape with a markedly hypoechoic internal echo texture in the thyroid and salivary glands [17,18], making them especially difficult to distinguish from IgG4-SS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that sonographic findings of PTL were correlated with pathologic findings. Orita et al (33) and Nam et al (29) indicated that the hypoechoic areas of PTL were consistent with lymphoepithelial lesions containing neoplastic cells, whereas echogenic structures within or around the lesions were consistent with fibrotic tissue and normal thyroid tissue. Ota (9) reported a destructive linear pattern which might suggest the transformation of MALT lymphoma into a high-grade malignant lymphoma.…”
Section: A B C D E Fmentioning
confidence: 90%